INFLUENCES OF PERSONALITIES ON STUDENTS PERFORMANCE IN PAIRWORK AND GROUPWORK IN SPEAKING LESSONS OF FIRST-YEAR MAINSTREAM STUDENTS, FELTE, ULIS - Truong, Thi Phuong (2020)
The great demand for pairwork and groupwork in speaking lessons at FELTE, ULIS, VNUH and the shortcomings of first-year mainstream students in those activities has inspired this research paper. As one of the first studies conducted on influences of personality on students’ performance in pairwork and groupwork in speaking lessons, the research paper focuses on both influences perceived by students themselves and possible recommendations to overcome the problems raised by experienced teachers. For the accomplishment of these purposes, 52 first-year mainstream students and 2 experienced speaking teachers at Division 1, FELTE, ULIS, VNUH have taken part in the data collection process in terms of questionnaires, interviews and classroom observations. Afterwards, the data analysis detected that unstable-extraverted was the common trend of students’ personality. Besides, some and negative influences of personality types on students’ performance in pairwork and groupwork speaking activities were found out. Based on those influences, recommendations of diving groups and pairs as well as diving roles and tasks for students in pairwork and groupwork were raised by the speaking teachers to reduce the negative effects and increase positive ones.